Penyuluhan Tentang Middle East Virus Nipah di SMK Abdurrab - Gina Adriana (PPNI UNIMMAN, 2024)
Middle East Respiratory Syndrome (MERS) and Nipah virus are two zoonotic diseases that have the potential to be fatal and require special attention in prevention and treatment. This outreach aims to increase the knowledge of students and teachers at Abdurab Vocational School regarding MERS and the Nipah virus, including symptoms, methods of transmission, and preventive measures. Implementation methods include educational presentations, interactive discussions, and simulations of preventive actions. The results of the outreach showed a significant increase in participants' understanding and school readiness in dealing with potential outbreaks. Recommendations are provided for the implementation of strict health procedures and follow-up education.